Sociology of Education Analysis on the Deep Learning Approach to Teaching - Damanik, Fritz Hotman Syahmahita; Muhammad, Gibran (Journal of Sumatera Sociological Indicators, 2025)
Traditional educational methods often emphasize rote memorization and passive learning, leading to disengagement and limited critical thinking among students. The shift towards deep learning has emerged as a response to these challenges, promoting inquiry-based learning, active engagement, and personalized instruction. This study aims to analyze the Deep Learning Approach from the perspective of the Sociology of Education, examining its impact on student engagement, educational equity, and socialization. Using a literature review methodology, this research systematically collects and analyzes scholarly works published within the last six years. The findings indicate that deep learning enhances student motivation, fosters critical thinking, and contributes to a more inclusive education system. However, challenges such as technological disparities, teacher readiness, and ethical concerns surrounding data privacy remain significant barriers to implementation. Addressing these issues through collaboration between educators, policymakers, and technology developers is essential for maximizing the benefits of deep learning in education.